Penerapan Metode VIKOR untuk Menentukan Kelayakan Perpustakaan Sekolah Diakreditasi - Sukamto Sukamto; Aidil Fitriansyah; Avisha Delinda Jukris (JURNAL MEDIA INFORMATIKA BUDIDARMA, 2023)
School libraries should be accredited with the aim of improving the quality of libraries. Pekanbaru City Library and Archives Service (DISPUSIP) in determining a school library that deserves to be accredited is still done manually. For this reason, a decision support system (DSS) is needed. This study uses the VIKOR method by steps of making a decision matrix, normalizing the criteria weight, determining the normalization matrix, determining the utility, determining the VIKOR index, and ranking. The alternative used is nine (9) junior high schools, both public and private. The criteria used refers to the school library accreditation instruments issued by the National Library that consist of six (6) criteria, namely collections, library facilities and infrastructure, library services, library staff, library administration and management, and reinforcement. The results obtained for the SMP library are Sek 4, Sek 7 and Sek 5 which are eligible for accreditation.